PENGARUH MODEL PEMBELAJARAN EXPERIENTIAL LEARNING TERHADAP HASIL BELAJAR SISWA TEMA PERKEMBANGAN TEKNOLOGI DI KELAS III SD - Apri Sela Sragih; Anton Sitepu; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the effect of the experiential learning model on students’ learning outcomes with the theme of technology development. The research used the experimental quantitative research method. The results indicated that students’ learning outcomes by using the experiential model were in the very good category with an average of 0.885. Normality testing obtained a significant value of 0.5% as the student’s learning outcomes, which were 0.200 > 0.05. Based on the calculation, it can be seen that the significant value of students’ learning outcomes was normally distributed. In the correlation testing, the coefficient value was 0.833, which meant rcount > rtable 0.361. The results of t-test testing where rcount > rtable was 7.975 > 1.697, so Ha was accepted. It shows that there was a positive and significant effect of the Experiential Learning model on students’ learning outcomes themed on technology development at Class III of SDN 094097 Simpang Pongkalan Tongah Dolok Masagal in Simalungun in the academic year 2020/2021.